Pengukuran Kualitas Jasa Bengkel Sepeda Motor SM di Kota Padang dengan Metode Servqual - Agus Sutanto (Jurnal Optimasi Sistem Industri, 2011)
This paper is concerned with the measurement of customer satisfaction a motorcycle repair shop in the city of Padang on the quality of service received by the SERVQUAL method. The method was developed in the 1980s by Zeithaml, Parasuraman & Berry used a questionnaire to measure quality of service. With this, it is known how big the gap (gap) that exists between perceptions and expectations of customers of a service company. Method of quantitatively measuring the quality of this service, contains dimensions such as tangibles (physical facilities and personnel), responsiveness (responsiveness), realibility (reliability), assurance (security) and empathy (empathy). The purpose of the use of the SERVQUAL dimensions is to make program improvements in the control of service-oriented to customer satisfaction, as one of the company's strategy to empower Total Quality Service. From the analysis of 84 samples without weighting the data of interest can be concluded that there is a gap between perception with expectations in every dimension. The sequence starts from the dimensions of each dimension with the largest gap is tangible dimension, followed by the dimensions of assurance, reliability, empathy and responsiveness of the last dimension. The average total gap of each dimension is equal to -0.8664. This suggests that the quality of service expected by customers has not been achieved. From the analysis of the value obtained by the dimensional weight of the interests of tangible (physical facilities and personnel) should get the greatest attention to be fixed.